Influence of Cell Size on Mechanical and Piezoelectric Properties of PZT and LNKN Ceramic Foams. Issue 10 (7th July 2017) - Eichhorn, Franziska; Biggemann, Jonas; Kellermann, Simone; Kawai, Akinobu; Kato, Kensuke; Kakimoto, Kenichi; Fey, Tobias
Abstract : Piezoceramic foams made of lead zirconate titanate (PZT) and lithium sodium potassium niobate (LNKN‐6) containing an open porosity >75 vol% are manufactured with varying cell size from 1369 to 265 μm and accordingly, strut size from 346 to 46 μm by replica method. Pore size distribution and strut thickness are determined by X‐ray micro tomography investigations of PZT foams with 10, 30, 45, and 80 pores per inch (ppi). Fracture strengths σb between 0.29 and 1.52 MPa (PZT) and 0.04 and 0.07 MPa (LNKN‐6) are determined by compression test and compared to Gibson and Ashby's model of open‐ and closed‐cell foams and in dependence of the cell size. The longitudinal and transversal coupling coefficients d33 and d31 decrease in a range of 38 to 178 pCN −1 or −13 to −100 pCN −1 compare to dense reference material. In dependence of the cell size, the values of the coupling coefficients change about 79–93%. The relative permittivity decreases 93% by decreasing the cell size of the PZT and LNKN‐6 foams. Abstract : Piezoceramic foams of PZT and LNKN‐6 (porosity >75 vol%) are manufactured by replica method. Depending on the cell size fracture strengths σb varied between 0.29 and 1.52 MPa (PZT) and 0.04 and 0.07 MPa (LNKN‐6), as well the longitudinal and transversal coupling coefficients d33 and | d31 | decreased in a range of 38 to 178 pCN −1 or −13 to −100 pCN −1 .